Assemblies of 1,4-Bis(diarylamino)naphthalenes and Aromatic Amphiphiles: Highly Reducing Photoredox Catalysis in Water - Hyodo, Yuki; Takahashi, Keigo; Chitose, Youhei; Abe, Manabu; Yoshizawa, Michito; Koike, Takashi; Akita, Munetaka (Synlett, 2021)
Host–guest assemblies of a designed 1,4-bis(diarylamino)naphthalene and V-shaped aromatic amphiphiles consisting of two pentamethylbenzene moieties bridged by an m-phenylene unit bearing two hydrophilic side chains emerged as highly reducing photoredox catalysis systems in water. An efficient demethoxylative hydrogen transfer of Weinreb amides has been developed. The present supramolecular strategy permits facile tuning of visible-light photoredox catalysis in water.
Keywords: photoredox catalysis; supramolecular catalysts; organophotocatalysis; radical reaction; Weinreb amides; demethoxylation